MEASUREMENT OF THE EFFECTIVENESS OF PUBLIC AID FOR FARMS IN POLAND - Marek Wigier; Marian Podstawka (Polityki Europejskie, Finanse i Marketing, 2021)
Agricultural policy is an attempt to put into practice the laws of economic theory, in order to achieve goals defined by the State. This research, carried out on a sample of four groups of Polish farms, contributes to the question of how to improve short-term economic policy in order to stimulate market mechanisms for the long-term development of the sector. Using data from the Polish FADN for 2008-2019, the authors of the study apply the modified PSM method to determine the economic effects of changes taking place on farms. The research indicates that effective investments are the source of long-term development and economic success. At the same time, it shows that economic entities, by optimizing their microeconomic objective function, adjust investments to the objectives of public aid, which reduces the effectiveness of the use of financial resources.